The nun in the synagogue : Judeocentric Catholicism in Israel - Polyakov, Emma O'Donnell (The Pennsylvania State University Press, 2020)
"A study of Catholic perceptions of Jews, Judaism, and Israel, offering an exploration of biographical narratives and reflections on Holocaust trauma, conversion, Zionism, and religious identity"--